Pengembangan Aplikasi untuk Sistem Informasi Manajemen Biro Umroh dan Haji: Kasus Biro Umroh Farfasa Tour Kabupaten Tuban - Dimas Yuda Wahyu Cakra Buana; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Indonesia is a country dominated by a Muslim population, especially in Java, especially East Java Province. In 2014, there were 36,472,783 people who follow Islam based on a survey conducted by the Ministry of Religious Affairs and BPS East Java. While in 2019 the same survey was conducted again and found as many as 37,558,874 people who follow Islam. This figure also contributes to the number of people who perform Umrah to the holy land. Therefore, Farfasa Tour Agency as one of the religious tourism service providers has several problems in management. There are frequent problems of agency customers not being able to get information about the schedule, too often going back and forth to the agency office to make sure the data is correct, and recording loans that are often missed. Therefore, an information system application is needed that is expected to help Farfasa Umroh Agency to solve the problem. The information system is developed using the waterfall method which will be developed on an Android-based platform and website. Information system development will go through the stages of needs analysis, design, implementation, and testing. Application development on Android will be native using the Kotlin programming language. The development of web-based applications will use the JavaScript programming language that uses ReactJs to build the user interface.